Revisiting persistent salmonella infection and the carrier state: What do we know? - Foster, Neil; Tang, Ying; Berchieri, Angelo [UNESP]; Geng, Shizhong; Jiao, Xinan; Barrow, Paul (MDPI, 2021)
One characteristic of the few Salmonella enterica serovars that produce typhoid-like infections is that disease-free persistent infection can occur for months or years in a small number of individuals post-convalescence. The bacteria continue to be shed intermittently which is a key component of the epidemiology of these infections. Persistent chronic infection occurs despite high levels of circulating specific IgG. We have reviewed the information on the basis for persistence in S. Typhi, S. Dublin, S. Gallinarum, S. Pullorum, S. Abortusovis and also S. Typhimurium in mice as a model of persistence. Persistence appears to occur in macrophages in the spleen and liver with shedding either from the gall bladder and gut or the reproductive tract. The involvement of host genetic background in defining persistence is clear from studies with the mouse but less so with human and poultry infections. There is increasing evidence that the organisms (i) modulate the host response away from the typical Th1-type response normally associated with immune clearance of an acute infection to Th2-type or an anti-inflammatory response, and that (ii) the bacteria modulate transformation of macrophage from M1 to M2 type. The bacterial factors involved in this are not yet fully understood. There are early indications that it might be possible to remodulate the response back towards a Th1 response by using cytokine therapy.
Keywords: Carrier state; Dublin; Gallinarum; Immunity; Pullorum; Salmonella; Typhi; Typhoid